Designing and applying technology for prevention: lessons learned in AEQUIPA and its implications for future research and practice - Meyer, Jochen; Ratz, Tiara; Pauls, Alexander; Hellmers, Sandra; Boll, Susanne; Fudickar, Sebastian; Hein, Andreas; Bauer, Jürgen M.; Koppelin, Frauke; Lippke, Sonia; Peters, Manuela; Pischke, Claudia Ruth; et al. (Frontiers in Public Health, 2022)
Almost all Western societies are facing the challenge that their population structure is changing very dynamically. Already in 2019, ten countries had a population share of at least 20 percent in the age group of 64 years and older. Today's society aims to improve population health and help older people live active and independent lives by developing, establishing, and promoting safe and effective interventions. Modern technological approaches offer tremendous opportunities but pose challenges when preventing functional decline. As part of the AEQUIPA Prevention Research Network, the use of technology to promote physical activity in older people over 65 years of age was investigated in different settings and from various interdisciplinary perspectives, including technology development and evaluation for older adults. We present our findings in three main areas: (a) design processes for developing technology interventions, (b) older adults as a user group, and (c) implications for the use of technology in interventions. We find that cross-cutting issues such as time and project management, supervision of participants, ethics, and interdisciplinary collaboration are of vital importance to the success of the work. The lessons learned are discussed based on the experiences gained in the overall AEQUIPA network while building, particularly on the experiences from the AEQUIPA sub-projects TECHNOLOGY and PROMOTE. Our experiences can help researchers of all disciplines, industries, and practices design, study and implement novel technology-based interventions for older adults to avoid pitfalls and create compelling and meaningful solutions.
Gesehen am 15.02.2023